Optimizing Chitosan production from insect-derived chitin - Lawal, Anako Opotu; Jasper, Enebi E; Onwuka, Jude Chinedu C; Ijege, King O; Emeachi, Francis Chidera; Abayomi, Adeniyi Taiwo (Bangladesh Journal of Scientific and Industrial Research, 2025)
Chitosan is an emerging raw material with increasing global demand, traditionally derived from crustaceans. Its production faces challenges such as high cost and inconsistent yields, necessitating the search for new chitosan precursors. This study investigates Melanoplus differentialis, a differential grasshopper, for sustainable chitosan production. Chitin was extracted from M. differentialis via sequential demineralization, deproteination, and decolorization, and then deacetylated. Response Surface Methodology (RSM), using the Box-Behnken design, was used to optimize NaOH concentration, NaOH:Chitin ratio, and deacetylation time. Statistical analysis identified NaOH concentration as the most significant factor influencing yield. The optimal process conditions of 40.5% NaOH, 16.8 mL/g NaOH: chitin ratio, and 69.3 minutes resulted in 60.62±0.79% chitosan yield. FTIR confirmed the transformation of chitin to chitosan. This study shows M. differentialis as a promising, unconventional chitosan precursor. Bangladesh J. Sci. Ind. Res. 60(3), 213-224, 2025